Mitral Regurgitation and its Predictors after Acute Myocardial Infarction in the Era of Coronary Intervention - Kafle, Ram Chandra; Jwarchan, Bishnu; Sharma, Dibya (Nepal Journal of Medical Sciences, 2021)
Introduction Mitral regurgitation is one of the common complications of acute Myocardial infarction but a very limited study was published about its prevalence and associated factors from Nepal. Methods A prospective cross-sectional study was conducted in admitted patients of the cardiology unit, Manipal Teaching Hospital from 01-06- 2020 to 15-09-2021. All cases of first time acute myocardial infarction who were presented within 12 hours of symptom onset and undergone revascularization with the coronary intervention were selected for the study Results A total of 219 patients with a mean age of 60.55± 12.5 years were taken for study. Moderate to severe mitral regurgitation was detected in 60 (27.4%) cases. The most common risk factors among responders were overweight followed by low high-density lipoprotein and smoking. Age >65yrs [OR:8.26(95%CI, 1.82-37.52); p=0.006], female gender [OR:2.05(95% CI,1.12-3.76); p=0.019], pre-obesity [OR: 2.43(95% CI, 1.14-5.17); P=0.019], longer ischemic time of >6 hrs [OR: 4.57(95%CI, 2.10-9.91); P= 0.001] and involvement of infero-posterior wall[OR: 3.04(95%CI, 1.61-5.774); P= 0.001] and left circumflex artery involvement [OR: 7.67(95%CI, 3.15-18.63); P= 0.001] were significantly associated with moderate to severe ischemic mitral regurgitation. Conclusion Mitral regurgitation is a common complication of acute myocardial ischemia. Elderly age, Female gender, longer ischemic time of more than six hours, involvement of infero-posterior wall and left circumflex artery was significantly associated with moderate to severe mitral regurgitation.